2016
DOI: 10.1038/onc.2016.452
|View full text |Cite|
|
Sign up to set email alerts
|

Transamidase site-targeted agents alter the conformation of the transglutaminase cancer stem cell survival protein to reduce GTP binding activity and cancer stem cell survival

Abstract: Type 2 transglutaminase (TG2) is an important cancer stem cell survival protein that exists in open and closed conformations. The major intracellular form is the closed conformation that functions as a GTP-binding GTPase and is required for cancer stem cell survival. However, at a finite rate, TG2 transitions to an open conformation that exposes the transamidase catalytic site involved in protein-protein crosslinking. The activities are mutually exclusive, as the closed conformation has GTP binding/GTPase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
134
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(139 citation statements)
references
References 55 publications
(164 reference statements)
3
134
0
Order By: Relevance
“…The link between TG2 and CSCs was recorded in other solid tumors. For example, TG2 upregulation was also recorded in the highly tumorigenic subpopulation of CD44 + /CD24 − breast CSCs characterized by self-renewal and mammosphere-forming capacity (13), in epidermal and glioblastoma CSCs, where it promoted spheroid proliferation and tumor formation (14,15). The connection between TG2 and chemotherapy or radiation-resistance in cancer cells (16) was attributed to activation of the NF-κB survival pathway (17,18) and of “outside-in” signaling (19), being consistent with the chemo-resistant phenotype of CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The link between TG2 and CSCs was recorded in other solid tumors. For example, TG2 upregulation was also recorded in the highly tumorigenic subpopulation of CD44 + /CD24 − breast CSCs characterized by self-renewal and mammosphere-forming capacity (13), in epidermal and glioblastoma CSCs, where it promoted spheroid proliferation and tumor formation (14,15). The connection between TG2 and chemotherapy or radiation-resistance in cancer cells (16) was attributed to activation of the NF-κB survival pathway (17,18) and of “outside-in” signaling (19), being consistent with the chemo-resistant phenotype of CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy induced GSCs death with subsequent significant decrease in neurosphere proliferation compared to either radiation or temozolomide treatment alone. Recent data in a different cancer model showed that the GTP-binding activity, associated with a closed conformation of TG2, but not the transamidase activity was required for epidermal CSC (ECSC) survival and spheroid formation [5]. The binding of irreversible inhibitors (NC9, VA4, and VA5) to the catalytic site of TG2 promoted a shift from its closed to an open conformation and led to a reduction in the survival and proliferation of ECSCs [5].…”
Section: Figurementioning
confidence: 99%
“…Recent data in a different cancer model showed that the GTP-binding activity, associated with a closed conformation of TG2, but not the transamidase activity was required for epidermal CSC (ECSC) survival and spheroid formation [5]. The binding of irreversible inhibitors (NC9, VA4, and VA5) to the catalytic site of TG2 promoted a shift from its closed to an open conformation and led to a reduction in the survival and proliferation of ECSCs [5]. The complex between TG2, fibronectin and integrins has also been proposed as a functional cancer target and inhibitors for this proteinprotein interaction are being developed [6].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations